The effect of comprehensive psychological interventions on the mental health of the community elderly - Zhang, Zi-Ming; Liu, Hui-Jun; Li, Gang; He, Ying; Guo, Xin; Zhao, Fang; Luo, Ying-Jie (Frontiers in Psychiatry, 2024)
Objective To observe the intervention effect of comprehensive psychological interventions on the mental health of the elderly population. Methods 133 elderly aged 60 and above in two urban districts of Tianshui City from January 2020 to December 2020 were selected and divided into the intervention group (n=67) and the control group (n=66). The intervention group received comprehensive psychological interventions, with no intervention given to the control group. The anxiety rate, depression rate, loneliness rate and happiness rate of the two groups were collected and compared pre- and post-intervention. Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), University of California, Los Angeles Loneliness Scale (UCLA) and Memorial University of Newfoundland Scale of Happiness (MUNSH) were used to compare the psychological status of the elderly pre- and post-intervention. Results Differences in the inter-group main effects and time-point main effects for SAS, SDS, UCLA, and MUNSH scores of the intervention group were significant (all p<0.05). The SAS, SDS, and UCLA scores of the intervention group were higher than those of the control group after intervention. Meanwhile, the SAS and SDS scores of the intervention group were lower than those of the control group after intervention (all p<0.05). Moreover, the MUNSH score of the intervention group was higher than that of the control group at 1-year follow-up post-intervention (p<0.05). Compared with pre-intervention values, the proportions of anxiety, depression loneliness, and happiness in the intervention group were improved at 1-year follow-up post-intervention (all P<0.05). Conclusion This study provides basis and important support for further investigations and the monitoring of health indicators in a population as fragile as the elderly. Targeted comprehensive psychological interventions can improve the negative emotions of community-dwelling elderly and maintain their physical and mental health. The “community-hospital linkage” mental health service model can improve the mental health status of community-dwelling elderly.